Study of the Ethnoscience Learning Approach About the Keris Yogyakarta for Chemistry Learning in High School - Kamaludin, Agus; Sriyati, Siti; Liliawati, Winny (Journal of Educational Chemistry (JEC), 2024)
This research aims to determine chemistry teachers' perceptions of ethnoscience-based learning approaches and the characteristics of the Keris Yogyakarta, as well as to examine its potential for high school chemistry education. This qualitative study involves ten high school chemistry teachers in Yogyakarta. Data collection techniques included questionnaires, interviews, and analysis of the high school chemistry curriculum. The research instruments used were survey sheets and interview guidelines. The data were analyzed using qualitative methods of Miles and Huberman. The results show that chemistry teachers have a positive perception of the ethnoscience approach. The Keris can serve  as a thematic element to introduce Yogyakarta culture in chemistry learning. Relevant chemical topics include elemental chemistry and redox reactions. The chemical elements or compounds involved in making the Keris include iron, steel, nickel, arsenic, citric acid, and ascorbic acid. Ethnoscience learning about the Keris provides students with knowledge about applying chemical concepts in its manufacture, integrating local knowledge and culture, and helping students understand chemical concepts more easily and engagingly. Additionally, ethnoscience learning about the Keris can increase students' appreciation and concern for Indonesia's cultural heritage.